Prospects and Challenges of Mushroom Production in Kuruwita, Sri Lanka: Comparative Report on Two Consecutive Years - Thilakaratna, W.S.; Pathirana, P.B.M. (University of Jaffna, 2018)
Global mushroom production has expanded rapidly in last few decades with the introduction of new mushroom varieties. However, Sri Lanka mainly relies on Oyster (Pleurotus ostreatus) and Abalone (Pleurotus cystidiosus) cultivation. It is believed that many of the mushroom farmers in Sri Lanka already gave up the business due to various issues related to production and marketing. Hence, the current study was executed from 03rd to 10th of April 2017 and 13th to 16th of February 2018 to identify the problems and challenges faced by the mushroom farmers in Kuruwita division of Sri Lanka. Direct interviews using structured questionnaire were used to collect information from 36 farmers in 2017. The sample contained 56% females and 44% males of different age categories, where, 39% and 33% belonged to age groups (31-40) and (41-50), respectively. Twenty five per cent of the farmers showed fulltime involvement, while, rest involved in mushroom cultivation as a part time job. However, only 19 farmers are still involved in the business (during survey in 2018) out of 36 farmers interviewed in 2017. Monthly average income of the farmers of this area was Rs. 16,777 in 2017 and Rs. 14,210 in 2018. Major problems and challenges faced by the farmers were lack of knowledge in mushroom cultivation and disease management, lack of financial assistance, difficulties in finding proper local market and producing value added mushroom products.
Keywords: Kuruwita; Mushroom; Pleurotus cystidiosus; Pleurotus ostreatus; Sri Lanka